Adipocytokines in obstructive sleep apnea: A systematic review and meta-analysis. (March 2023) - Janmohammadi, Parisa; Raeisi, Tahereh; Zarei, Mahtab; Nejad, Maryam Mofidi; Karimi, Roya; Mirali, Zahra; Zafary, Reza; Alizadeh, Shahab
Abstract: Background and aim: Adipocytokines play an important role in obstructive sleep apnea (OSA) by mediating inflammatory responses. Previous studies have reported that OSA is related to a change in the serum levels of adipocytokines; however, the results are still controversial. This meta-analysis aimed to assess the relationship between OSA and circulating level of adipocytokines in adults and children. Methods: A comprehensive search was conducted in databases of Medline/PubMed and Scopus for pertinent articles published since their inception to July 2022. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were used to assess the strength of the relationship between the concentrations of adipocytokines with OSA. Results: In the overall analysis, contrary to IL-10, which showed a significant reduction, IL-1β, IL-4, IL-8, IL-17, and IFN- gamma showed higher levels in OSA patients in comparison with control groups (p <0.05). For adults, IL-1β, IL-8, IL-17, IL-18, vaspin, visfatin, and chemerin were linked to a greater serum levels in patients with OSA, while, IL-5 and IL-10 were detected significantly lower in adults with OSA in comparison with healthy adults (p <0.05). In children with OSA, the serum levels of IL-4, IL-8, IL-12, IL-17, IL-23, and IFN-gamma were significantly higher than healthy children (p <0.05). Conclusion: The levels of inflammatory markers were found to be higher in OSA patients compared with control individuals, suggesting that adipocytokines may contribute to the pathology of OSA. Highlights: OSA patients have higher levels of inflammatory markers compared with control individuals. The most considerable inflammatory cytokines elevating in OSA patients are IL-8, IL-17 and IL-1β. Vaspin, visfatin, and chemerin are linked to a greater serum levels in adult patients with OSA. The anti-inflammatory cytokine IL-4 can exert proinflammatory effect in OSA patients.